2014
DOI: 10.1007/s11033-014-3543-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of epithelial tight junctions involved in pathogen infections

Abstract: Tight junctions (TJs) are sealing complexes between adjacent epithelial cells, functioning by controlling paracellular passage and maintaining cell polarity. These functions of TJs are primarily based on structural integrity as well as dynamic regulatory balance, indicating plasticity of TJ in response to external stimuli. An indispensable role of TJs involved in pathogen infection has been widely demonstrated since disruption of TJs leads to a distinct increase in paracellular permeability and polarity defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 168 publications
2
50
0
2
Order By: Relevance
“…In fact, higher levels of antiproteases have been associated with HIV resistance in highly exposed seronegative female sex workers (23,44). Furthermore, the anti-inflammatory effects of these factors may also promote the maintenance of the epithelial barrier throughout the genital tract, which is also critical for defense against pathogen infection, including HIV (45). Indeed, our study also found proteins associated with barrier integrity to be overabundant during the follicular phase.…”
Section: Discussionsupporting
confidence: 49%
“…In fact, higher levels of antiproteases have been associated with HIV resistance in highly exposed seronegative female sex workers (23,44). Furthermore, the anti-inflammatory effects of these factors may also promote the maintenance of the epithelial barrier throughout the genital tract, which is also critical for defense against pathogen infection, including HIV (45). Indeed, our study also found proteins associated with barrier integrity to be overabundant during the follicular phase.…”
Section: Discussionsupporting
confidence: 49%
“…[22] In the present study, the expression of claudin-1, occludin and ZO-1 in the intestinal mucosal significantly decreased in patients with infectious complications and those in the NACT group. Members of the claudin family are the most important transmembrane proteins, which contribute to several aspects of TJs permeability.…”
Section: Discussionsupporting
confidence: 48%
“…Our results indicated that 450 mg kg −1 nano‐ZnOs and 3000 mg kg −1 ZnO protected small intestinal morphology by increasing the villus height, which was consistent with the results reported by Long et al ., who reported that the supplemental nano‐ZnOs of 500 mg kg −1 protected against intestinal injury. Enterohemorrhagic E. coli (EHEC) is an enteric pathogen that leads to diarrhea mediated by intestinal epithelial barrier disruptions during the weaning phase . Kim et al .…”
Section: Discussionmentioning
confidence: 99%